Issue Information. Issue 1 (17th December 2020) - Unknown
Abstract : Cover : In Gabler et al. (http://doi.org/10.1002/cpbi.108 ), the image shows submission and output pages of MODELLER. The shown input (A ) was generated as described in Basic Protocol 2, step 8. The 3D structural model built for P. syntrophicum FtsZ is shown in B .